An historical survey of the organs, organists and music of St. George's Cathedral, Cape Town, from 1834 to 1952 - Smith, Barry, 1939- (Rhodes University, Faculty of Humanities, Department of Music, 1969)
From Introduction: The first recorded Church of England service at the Cape took place in 1749, but for almost a century after that date Anglicans had no place of worship of their own. From about 1807 onwards the Groote Kerk in Adderley Street was regularly lent to the Chaplain on Sundays and the Kerkraad even allowed their bells to be rung to inform 'the British that it was time for their service'. In October 1827, for the first time in history, a bishop of the Church of England visited Cape Town. This was Dr. J.T. James, Bishop of Calcutta, who landed for a few days on his first voyage to India and was met by the Governor and his staff in great state. A meeting was held at which Bishop James was present and the eighteen gentlemen discussed proposals for the building of an English Church in Cape Town. "It was proposed that the building should hold at least 1,000 people. The Bishop said that the Home Government would grant ground and half the expenses... He reminded them of their obligation to the Dutch Church, who for so many years had allowed them to use their sanctuary, and he exhorted them to be active and persevering and remain attached to the doctrine and discipline of the Church of their forefathers, that venerable Church based on the foundation of Christ and His Apostles." As a result of t his meeting the Governor gave the site in the Gardens (at the foot of the Avenue) on which St . George's Cathedral now stands, and the site was consecrated by Bishop James on October 23rd, just before he sailed for Calcutta . "But after his departure the glow faded away, difficulties and quarrels appeared... and the scheme was shelved for two years." However, on St. George's Day, 23rd April 1830, the foundation stone of St. George's Church was laid by the Governor, Sir Lowry Cole,with military and Masonic honours. A triumphal arch was erected and troops lined the streets through which the procession was to pass. The name of the street at the head of which the Cathedral stands was changed from Bergh Street to St. George' s Street, and the contract was exclusive of enclosure, gates, bells and organ, but including pulpit, reading and clerk 's desks and all the work of the altar."
Keywords: St. George's Cathedral (Cape Town, -- South Africa); Organ (Musical instrument) -- South Africa -- Cape Town -- History; Organists